Combined accuracy of Procalcitonin and Quick Sequential Organ Failure Assessment (qSOFA) in predicting 3-days in-hospital mortality in suspected sepsis. - Ali Memon, Tauseef; Butt, Saman; Khalid, Imtiaz; Dehrab, Nawaf; Afsheen, Noor; Jamil, Maryam; Ehsan Ulhaq (International Journal of Endorsing Health Science Research, 2021)
Background: Early identification of sepsis is important for initiating appropriate treatment for decreasing the risk of in-hospital mortality. To determine the diagnostic accuracy of procalcitonin (PCT) and quick sequential organ failure assessment (qSOFA) in predicting 3-days in-hospital mortality in suspected sepsis. Methodology: A cohort study was conducted at the emergency department of Ziauddin University Hospital, Karachi. One-hundred and thirty-two suspected cases of sepsis having age 18-75 years were selected through convenience sampling. PCT level and qSOFA score were obtained for predicting 3-days in-hospital mortality. Results: Of the study patient, 50.8% were male, and 49.2% were female, with a mean age of 53.7 ± 18.3 years. The mean qSOFA score was 1.8 ± 0.5, and the mean PCT level was 2.7 ± 12.5 ng/ml. The combined QSOFA and PCT 3-days in-hospital mortality prediction was 31.1%, while the actual mortality rate was 28.0%. The combined qSOFA score and PCT level sensitivity was 62.2%, specificity 81.1%, positive predicted value 56.1%, negative predicted value 84.7%, and diagnostic accuracy 75.8%. Conclusion: The combined use of QSOFA and PCT improves the 3-day in-hospital mortality prediction in suspected cases of sepsis.